Cosolubilization synergism occurrence in codesorption of PAH mixtures during surfactant-enhanced remediation of contaminated soil. (February 2016) - Liang, Xujun; Guo, Chuling; Wei, Yanfu; Lin, Weijia; Yi, Xiaoyun; Lu, Guining; Dang, Zhi
Abstract: Surfactant-enhanced remediation (SER) has been widely applied in decontaminating PAH-polluted soil. Most researches focus on evaluating washing efficiency without considering pollutants' mutual interaction. This study aims to investigate cosolubilization effect between phenanthrene (Phe) and pyrene (Pyr) in nonionic surfactant Triton X-100 (TX100) solution on their codesorption performance from soil. Cosolubilization experiment showed that, when cosolubilized, solubility of Phe and Pyr in TX100 increased by 15.38% and 18.19%, respectively, as quantified by the deviation ratio of molar solubilization ratio in single and binary solute solubilization systems. The synergism may be due to the enlarged micelle volume caused by PAHs solubilized in the shell region of the micelle. The cosolubilization effect was further observed in the soil washing process. The strengthened TX100 solubilization capacity towards Phe and Pyr could increase the two PAHs' codesorption efficiency from soil, accompanied by synergistic extent of 6–15%. However, synergism in codesorption was weaker than that observed in the cosolubilization system, which may be related to surfactant loss to soil and PAH partition into soil organic matter and the sorbed surfactants. The improved remediation performance during codesorption of mixed PAHs implies the significance of combining PAHs' mutual interaction into evaluating SER, which may reduce the surfactant washing concentration and save remediation cost. Highlights: Cosolubilization of phenanthrene and pyrene in Triton X-100 showed synergism. Cosolubilization synergism could improve surfactant washing efficiency. Synergistic extent was lower during codesorption than that in cosolubilization. Synergism in codesorption depended on surfactant loss, soil and PAH properties.